Epidural Analgesia and Subcutaneous Heparin 3 Times Daily in Cancer Patients With Acute Postoperative Pain. (October 2018) - Su, Jackson; Soliz, Jose M.; Popat, Keyuri U.; Gebhardt, Rodolfo
Abstract : The use of epidural analgesia in conjunction with subcutaneous administration of unfractionated heparin 3 times per day could increase the risk of spinal epidural hematoma, but insufficient patient experience data exist to determine this. We retrospectively reviewed the incidence of spinal epidural hematoma in 3705 cases at our institution over a 7-year period of patients receiving acute postoperative epidural analgesia and heparin 3 times per day. No cases of spinal epidural hematoma were reported (95% CI, 0–0.0009952).